1994
DOI: 10.1007/bf01268087
|View full text |Cite
|
Sign up to set email alerts
|

Transganglionic labelling of primary sensory afferents in the rat lumbar spinal cord: comparison between wheatgerm agglutinin and the I-B4 isolectin fromBandeiraea simplicifolia

Abstract: We recently reported that the I-B4 isolectin from Bandeiraea simplicifolia could be used as a transganglionic neuronal tracer which appears to be selective for unmyelinated cutaneous afferents (C fibres) and their terminals in the superficial dorsal horn. As terminals in the superficial dorsal horn are also labelled by wheatgerm agglutinin, we sought to compare these two neuronal tracers. Three days after the injection of 1% wheatgerm agglutinin-HRP or 1% BSI-B4-HRP into the sciatic nerve of adult rats the lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 43 publications
(53 reference statements)
5
22
0
Order By: Relevance
“…The results of this study confirm previous reports of BSI-B 4 binding in the rat, mouse, and rabbit (Streit et al, 1985;Kruger, 1988, 1990;Plenderleith et al, 1992;Plenderleith and Snow, 1993;Kitchener et al, 1994;Wang et al, 1994), and are entirely consistent with studies reporting BSI-B 4 binding in dorsal root ganglia and spinal cord of the chicken (Scott et al, 1990), echidna (Ashwell and Zhang, 1997), opossum (Knott et al, 1999), and rhesus monkey (Tong et al, 1999). Furthermore, recent studies have reported BSI-B 4 binding sites on human primary sensory neurones collected either post-mortem or from patients undergoing surgery (Yiangou et al, 2000;Alavi et al, 2001).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of this study confirm previous reports of BSI-B 4 binding in the rat, mouse, and rabbit (Streit et al, 1985;Kruger, 1988, 1990;Plenderleith et al, 1992;Plenderleith and Snow, 1993;Kitchener et al, 1994;Wang et al, 1994), and are entirely consistent with studies reporting BSI-B 4 binding in dorsal root ganglia and spinal cord of the chicken (Scott et al, 1990), echidna (Ashwell and Zhang, 1997), opossum (Knott et al, 1999), and rhesus monkey (Tong et al, 1999). Furthermore, recent studies have reported BSI-B 4 binding sites on human primary sensory neurones collected either post-mortem or from patients undergoing surgery (Yiangou et al, 2000;Alavi et al, 2001).…”
Section: Discussionsupporting
confidence: 82%
“…The termination pattern of BSI-B 4 binding primary sensory neurones in the spinal cord correlates closely with that of cutaneous nociceptors (Light and Perl, 1979;Sugiura et al, 1986;Kitchener et al, 1994). Furthermore, the vast majority of BSI-B 4 -labelled neurones also express the vanilloid receptor subtype 1, a molecule widely implicated in transduction of nociceptive stimuli (Guo et al, 1999;Michael and Priestly, 1999).…”
Section: Discussionmentioning
confidence: 83%
“…In addition, we found that 64 % of P2X 3 receptor-expressing trigeminal ganglion neurons also express IB4, suggesting that they are mainly non-peptidergic, unmyelinated afferents, since IB4 labelling is almost entirely limited to non-peptide unmyelinated afferents in the rat (Ambalavanar and Morris, 1993;Kitchener et al, 1993;Kitchener et al, 1994;Stucky and Lewin, 1999;Gerke and Plenderleith, 2001). This proportion is in agreement with previous reports in the rat (73 %, Ambalavanar et al, 2005) and mouse (70 %, Ruan et al, 2004) trigeminal ganglia, but contrasts with studies in the DRG where almost all P2X 3 -expressing neurons are IB4-positive in the mouse (99 %, Ruan et al, 2004), rat (>94 %, Bradbury et al, 1998;Vulchanova et al, 1998;Novakovic et al, 1999) and cat (88 %, Ruan et al, 2005).…”
Section: Discussion P2x 2 and P2x 3 Receptors Are Predominantly Locatmentioning
confidence: 83%
“…To determine the effect of RTX treatment on the δ-opioid receptors and Griffonia simplicifolia isolectin B 4 (IB 4 )-positive DRG neurons and primary afferent terminals in the spinal dorsal horn, double fluorescence labeling of δ-opioid receptors and IB 4 [a marker for unmyelinated primary neurons and afferent fibers (Kitchener et al, 1994;Kitchener et al, 1993)] was performed in the lumbar DRGs and spinal cords from three RTX-treated and three vehicle-treated rats 4 weeks after treatment. As described previously (Chen and Pan, 2006b;Chen et al, 2007b), each rat was intracardially perfused with 4% paraformaldehyde and 10% sucrose in 0.1 M PBS (pH 7.4) while under deep anesthesia with pentobarbital sodium (60 mg/ kg, i.p.).…”
Section: Double Fluorescence Labeling Of δ-Opioid Receptors and Ib 4 mentioning
confidence: 99%